Pembuatan dan Penyemprotan Disenfektan Sesuai Standar WHO dalam Penanganan dan Pencegahan Penyebaran Wabah Virus Corona-19 di Politeknik Negeri Cilacap - Agus Santoso; Auliya Kahfi; Lulu Qurrota Ayuni; Dodi Satriawan (Politeknik Negeri Cilacap, 2021)
Every educational institution, both state and private, has the same main task and is important in carrying out lecture activities. These three main tasks are in the form of lecture or academic activities, research activities, and community service activities. These three main activities are commonly referred to as Tridarma Perguruan Tinggi. To carry out these three activities or Tridarma Perguruan Tinggi, health and safety are needed at work. It is known today that all parts of the world have experienced the outbreak of the Coronavirus disease 2019 or Covid-19. This has a very direct impact on the process of implementing Tridarma Perguruan Tinggi. To reduce the spread of the Covid virus outbreak, the actual action is needed that can prevent the transmission of the Covid virus outbreak. The government through the Ministry of Health issued 3M guidelines in preventing and reducing the spread of the Covid virus outbreak. 3M stands for wearing a mask, washing hands, and keeping your distance. However, 3M is not enough, there need to be other actions to prevent and reduce the spread of the Covid virus outbreak in safeguarding all the academics and students of the Cilacap State Polytechnic. One of the other forms of efforts taken in handling the spread of the Covid outbreak in the Cilacap State Polytechnic environment is the manufacture of WHO standard disinfectants and the holding of regular disinfectant spraying.